Effect of smoking status on immunotherapy for lung cancer: a systematic review and meta-analysis - Luo, Dachen; Yang, Dongmei; Cao, Dan; Gong, Zonglian; He, Fang; Hou, Yaqin; Lin, Shan (Frontiers in Oncology, 2024)
BackgroundRecent studies have yielded conflicting results regarding the relationship between smoking history and the effectiveness of immune checkpoint inhibitors (ICIs) for advanced lung cancer. While some studies have suggested that smoking may enhance the response to immunotherapy in patients with lung cancer, other findings indicate the contrary. Therefore, we conducted a systematic review and meta-analysis to thoroughly examine this association.MethodsWe searched the PubMed, Embase, and Scopus databases for clinical trials comparing immunotherapy with conventional chemotherapy as the primary treatment for advanced lung cancer. A random effects model was used to synthesize hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS). We also conducted predefined subgroup analyses to investigate the efficacy disparities between never-smokers and smokers who were administered immunotherapy alone or in combination with chemotherapy, as well as the differences between former and current smokers under similar treatment modalities.ResultsOur analysis included data from 17 Phase III clinical trials involving 10,283 patients. The findings indicate that immunotherapy benefits both smokers and never-smokers with lung cancer or non-small cell lung cancer, yielding pooled HRs for OS of 0.74 (95% CI: 0.59–0.92) and 0.73 (95% CI: 0.67–0.80), respectively. A significant interaction effect was not observed (HR: 0.98, 95% CI: 0.77–1.24, pinteraction = 0.14), and the tumor type, immunotherapy combination, and type of immunotherapy did not differ among the groups in the subgroup analyses. Similarly, both former and current smokers experienced a significant survival benefit from immunotherapy, with pooled HRs for OS of 0.79 (95% CI: 0.68–0.91) and 0.71 (95% CI: 0.59–0.87), respectively. However, a significant interaction effect was also not observed (HR: 0.91, 95% CI: 0.74–1.11, pinteraction = 0.14).ConclusionOur findings suggest that smoking status does not affect the effectiveness of immunotherapy for lung cancer treatment. However, additional high-quality clinical trials are needed to confirm this conclusion.Systematic review registrationhttps://inplasy.com/register/, identifier INPLASY2023110058.